Xanthoceras sorbifolia Husk Extract Incorporation for the Improvement in Physical and Antioxidant Properties of Soy Protein Isolate Films - Yingying Han; Wentao Yan; Yuping Hou; Dongmei Wang; Miao Yu (Foods, 2023)
With the increasing awareness of ecological and environmental protection, the research on eco-friendly materials has experienced a considerable increase. The objective of our study was to explore a novel soy protein isolate (SPI) film functionalized with antioxidants extracted from Xanthoceras sorbifolia husk (XSHE) as bio-based active packaging films. The films were evaluated in light of their structure, physical machinery, and antioxidant performance using advanced characterization techniques. The FTIR and microscopy results revealed the hydrogen-bond interaction between the SPI and XSHE and their good compatibility, which contributed to the improvement in various properties of the composite films, such as tensile strength (TS), UV blocking, and the water barrier property. As the XSHE content increased to 5%, the TS of the films dramatically increased up to 7.37 MPa with 47.7% and the water vapor permeability decreased to 1.13 × 10−10 g m m−2 s−1 Pa−1 with 22.1%. Meanwhile, the introduction of XSHE caused further improvement in the antioxidant capacity of films, and the release of active agents from films was faster and higher in 10% ethanol than it was in a 50% ethanol food simulant. Overall, SPI-based films functionalized with XSHE demonstrated promising potential applications in food packaging.